2020
DOI: 10.1364/ol.410013
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution imaging with an achromatic multi-level diffractive microlens array

Abstract: Compound eyes found in insects provide intriguing sources of biological inspiration for miniaturized imaging systems. Inspired by such insect eye structures, we demonstrate an ultrathin arrayed camera enabled by a flat multilevel diffractive microlens array for super-resolution visible imaging. We experimentally demonstrated that the microlens array can achieve large fill factor (hexagonal close packing with pitch=120µm), thickness of 2.6µm, and diffraction-limited (strehl ratio = 0.88) achromatic performance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…For practical applications, flat optical devices need to avoid using nanostructures whose aspect ratios are too large. It has been reported that multi-level diffractive lens (MDL) offers a method to design broadband achromatic flat lens [32,33]. MDL is generally made of many rings with different radii and heights, and achromatic focusing can be achieved by optimizing the radii and heights of these rings.…”
Section: Introductionmentioning
confidence: 99%
“…For practical applications, flat optical devices need to avoid using nanostructures whose aspect ratios are too large. It has been reported that multi-level diffractive lens (MDL) offers a method to design broadband achromatic flat lens [32,33]. MDL is generally made of many rings with different radii and heights, and achromatic focusing can be achieved by optimizing the radii and heights of these rings.…”
Section: Introductionmentioning
confidence: 99%